POTENSI SEL T MOBIL HER2 SPESIFIK MODIFIKASI CRISPR / CAS9 PD-1 / PD-L1 PEMBLOKIRAN SEBAGAI INOVASI TERAPI UVEAL MELANOMA - Muhammad AH Khoiruddin; Yusi Windya Febriyanti; Nafia Amalia (Journal Medical Universitas muhammadiyah Makassar, 2019)
Uveal Melanoma (UM) is the primary intraocular tumor most commonly found in adults. The combination of therapy, Brachytherapy, surgery, Tranpupillary Thermal Therapy (TTT), Proton Beam Theraphy has not produced satisfactory results. The discovery of HER2 receptors expressed by UM cells can be used as a specific antigen target for the treatment of CAR T-celss. However, the effectiveness of CAR T-cell immunotherapy in tumors results in immunosuppressive T cells caused by an increase in Programmed cell Death Ligand-1 (PD-L1). This literature review demonstrates the success of HER2-specific CART T Cells as UM therapeutic efforts capable of eliminating tumor cells. In addition, CRSPR / Cas9 PD-1 / PD-L1-blocking modified HER2-specific CAR T cells can be a gene innovation in UM sufferers. Further clinical trials are needed to prove the effectiveness of CRISPR / Cas9 PD-1 / PD-L1-Blocking modified HER2-specific CAR T Cells in the treatment of UM patients.Keywords: Uveal melanoma, CAR T cell, reseptor HER